Functional Outcomes After Revascularization Procedures in Patients With Hemorrhagic Moyamoya Disease. Issue 2 (15th April 2019) - Abhinav, Kumar; Furtado, Sunil V; Nielsen, Troels H; Iyer, Aditya; Gooderham, Peter A; Teo, Mario; Lee, Justin; Han, Summer S; Steinberg, Gary K
Abstract: BACKGROUND: Poor natural history of hemorrhagic Moyamoya disease (MMD) is related to high rehemorrhage rates between 32% and 61%. Postrevascularization, rehemorrhage rates reportedly decrease to 12% to 17%. OBJECTIVE: To evaluate long-term functional outcomes and rehemorrhage rates of hemorrhagic MMD patients treated with surgical revascularization and examine these in relation to clinical and radiological factors. METHODS: Patients treated surgically for hemorrhagic MMD over a 26-yr period were identified. Modified Rankin scale (mRS) was used to assess clinical status at presentation and functional outcomes. Multivariable regression analyses were performed to evaluate the risk factors associated with rehemorrhage rates and functional outcomes. RESULTS: A total of 104 patients (mean age: 38.04 yr) were identified. The mean mRS score at baseline was 1.3. Of 172 revascularized hemispheres, 157 (91.3%) were direct superficial temporal artery (STA)-middle cerebral artery (MCA) bypasses and the rest indirect. Over the mean follow-up of 61.4 mo, 8 of 104 patients (7.7%) experienced rehemorrhage with rehemorrhage rate per person-years of 1.9%. A total of 4 patients died with 1 related to rehemorrhage. At the last follow-up, mean mRS score improved to 1.1. No significant risk factors were identified in relation to the rehemorrhage rates ( P  < .05). The patients' initial mRS score was positively associated with mRS scores at the final follow-up ( P  < .001). STA-MCA direct bypass was associated with better performance status ( P  = .033). CONCLUSION: Rehemorrhage rate following surgical revascularization of the hemorrhagic MMD patients at 7.7% is lower compared with much higher natural history rates. Surgical revascularization improved patients' performance status. These outcomes support performing revascularization procedure with a preference for direct STA-MCA bypasses. Graphical Abstract: